Analisis Fleksibilitas Kerja, Motivasi Kerja, Reward Terhadap Kinerja Driver Transportasi Ojek Online - Anggoro Putro; Shofif S Akbar; Qristin Violinda (Yayasan Al Ma'arif Dawuhan, 2024)
This study aims to examine the influence of work flexibility, work motivation, and rewards on the performance of Maxim online drivers in Semarang City. The research adopts a quantitative method, with the population consisting of Maxim online drivers in Semarang in 2024. A sample of 100 drivers was selected using Slovin's formula. The sampling technique employed was probability sampling with a random sampling method, where members of the sample were chosen randomly without considering the strata within the population. Data analysis was conducted using SPSS for Windows version 27 software. The results indicate that work flexibility (X1) has a positive and significant effect on the performance of Maxim online drivers in Semarang City (Y) on a partial basis, with a significance value of 0.004. Conversely, work motivation (X2) does not have a significant influence on driver performance, as indicated by a significance value of 0.897. Meanwhile, rewards (X3) demonstrate a positive and significant impact on driver performance, with a significance value of 0.001. These findings underscore the importance of work flexibility and rewards in the context of Maxim online drivers in Semarang. Thus, work flexibility and an effective reward system play a crucial role in enhancing the performance of Maxim online drivers in Semarang. On the other hand, motivation does not significantly influence performance. This suggests that motivation requires a more strategic approach to generate a meaningful impact. Companies could leverage work flexibility and an effective reward system as part of their strategy to boost productivity and job satisfaction among drivers.